Business Development Strategy at PT BPRS ABC - Sentosa, Alam; Heryawan Asnawi, Yudha; Asikin, Zenal (Publikasi Indonesia, 2026)
PT BPRS ABC has recorded strong financing growth in the MSME sector; however, this expansion has not been matched by improved credit quality, as indicated by a persistently high Non-Performing Financing (NPF) ratio. This imbalance threatens the company’s financial stability and long-term sustainability, underscoring the need for a targeted and sustainable business strategy to strengthen performance and manage risk. This research aims to formulate the right business strategy for PT BPRS ABC to improve business performance, particularly through controlling the risk of non-performing financing. The study employed a qualitative case study design. Primary data were collected through in-depth interviews with management and relevant divisions, supplemented by secondary data from financial reports and internal documents. Analytical frameworks, including RBV, VRIO, Porter’s Five Forces, IFE, EFE, IE, SWOT, and QSPM, were integrated to identify internal and external factors influencing business performance and to formulate appropriate strategic alternatives. The results of the study show that PT BPRS ABC has several internal strengths, including a commitment to strengthening financing analysis based on the 5C principle, a focus on productive financing for MSMEs, and the support of a relatively experienced remedial department. On the other hand, there remain internal weaknesses in the form of a suboptimal Early Warning System (EWS), weak post-disbursement monitoring, and inadequate quality of customer data. Externally, the main opportunities stem from government policy support for MSMEs and the use of Financial Information Service Systems (FISS), while threats include competition from digital banks and fintech, regulatory pressures, and property sector risks.